Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik dengan Metode Profile Matching pada PT. KB Finansia Multi Finance Cabang Depok Divisi Operation - Ahmad Fauzi; Anis Listiana Wati; Syifah Fauziah; Syarif Hidayatulloh (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The success of a company is influenced by good HR management. The establishment of human resources with good quality is expected to improve the company's operational performance. The condition that is the company's problem in determining the best employees lies in the evaluation process is still carried out subjectively and manually, which makes the company difficult in determining the eligibility of an employee to be the best employee then a decision support system is needed to minimize problems in analyzing employee performance results. This research aims to provide convenience for the company to get optimal results and admit in determining the best employees at PT. KB Finansia Multi Finance uses the Profile Matching method. The population in this study is the staff operation of PT KB Finansia Multi Finance Depok which amounted to 35 employees and took 10 samples of employees of the staff administration. The results of this study used the Profile Matching method and determination using quantitative data from filling out questionnaires that in it contained several aspects of criteria such as work attitudes, abilities, performance and work experience and disseminated to 10 respondents consisting of superiors, peers, and office boys.